Menjembatani Data dan Makna - Khabibullah, Muttaqin; Alimin; Sholahuddin, Gus Malik Imam (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
Mixed Methods Research (MMR) faces significant challenges in integrating quantitative and qualitative findings, particularly when the two types of data produce conflicting interpretations. Although abductive logic has been widely discussed in qualitative research, its role as a systematic mode of reasoning for bridging data and paradigm tensions in MMR remains underexplored. This article aims to analyze the role of abductive logic across four major MMR models: convergent, sequential, embedded, and transformative. Using a conceptual review approach, the study demonstrates that abduction functions as an interpretive mechanism for simultaneous data conflicts in the convergent model; as a bridge for reinterpretation across research phases in the sequential model; as a trigger for critically re-evaluating dominant findings through minor data in the embedded model; and as an interpretive leap that challenges dominant meanings and opens spaces for emancipation in the transformative model. These findings underscore that abductive logic expands the interpretive scope of research outcomes and strengthens reflective and context-sensitive methodological integration, particularly in educational and social policy research.